Fish Oil-Derived Long-Chain n-3 Polyunsaturated Fatty Acids Reduce Expression of M1-Associated Macrophage Markers in an ex vivo Adipose Tissue Culture Model, in Part through Adiponectin - De Boer, Anna A.; Monk, Jennifer M.; Liddle, Danyelle M.; Power, Krista A.; Ma, David W. L.; Robinson, Lindsay E. (Frontiers in Nutrition, 2015)
Adipose tissue (AT) macrophages (ATM) play a key role in obesity-associated pathologies, and their phenotype can be influenced by the local tissue microenvironment. Interestingly, long-chain n-3 polyunsaturated fatty acids (LC n-3 PUFA) and the LC n-3 PUFA-upregulated adipokine, adiponectin (Ad), may mitigate excessive ATM inflammatory M1-polarization responses. However, to what extent LC n-3 PUFA and Ad work in concert to affect macrophage phenotype has not been examined. Thus, we used an established ex vivo AT organ culture model using visceral AT from mice fed a control (CON; 10% w/w safflower oil) n-6 PUFA-rich diet or an isocaloric fish-oil (FO; 3% w/w menhaden oil + 7% w/w safflower oil)-derived LC n-3 PUFA-rich diet to generate AT conditioned media (ACM). We then evaluated if CON or FO ACM affected macrophage polarization markers in a model designed to mimic acute (18 h ACM plus LPS for the last 6 h) or chronic (macrophages treated with LPS-challenged CON or FO ACM for 24 h) inflammation ± Ad-neutralizing antibody and the LPS-neutralizing agent, polymyxin B. In the acute inflammation model, macrophages treated with FO ACM had decreased lipid uptake and mRNA expression of M1 markers (Nos2, Nfκb, Il6, Il18, Ccl2 and Ccl5) compared with CON ACM (p≤0.05); however, these effects were largely attenuated when Ad was neutralized (p>0.05). Further, in the chronic inflammation model, macrophages treated with FO ACM had decreased mRNA expression of M1 markers (Nos2, Tnfα, Ccl2 and Il1β) and IL-6 and CCL2 secretion (p≤0.05); however, some of these effects were lost when Ad was neutralized, and were further exacerbated when both Ad and LPS were neutralized. Taken together, this work shows that LC n-3 PUFA and Ad work in concert to suppress certain M1 macrophage responses. Thus, future strategies to modulate the ATM phenotype should consider the role of both LC n-3 PUFA and Ad in mitigating obese AT inflammation.